Scaling of movement is related to pallidal γ oscillations in patients with dystonia - Brücke, Christof; Blahak, Christian (The journal of neuroscience, 2012)
Neuronal synchronization in the gamma (γ) band is considered important for information processing through functional integration of neuronal assemblies across different brain areas. Movement-related γ synchronization occurs in the human basal ganglia where it is centered at ∼70 Hz and more pronounced contralateral to the moved hand. However, its functional significance in motor performance is not yet well understood. Here, we assessed whether event-related γ synchronization (ERS) recorded from the globus pallidus internus in patients undergoing deep brain stimulation for medically intractable primary focal and segmental dystonia might code specific motor parameters. Pallidal local field potentials were recorded in 22 patients during performance of a choice-reaction-time task. Movement amplitude of the forearm pronation-supination movements was parametrically modulated with an angular degree of 30°, 60°, and 90°. Only patients with limbs not affected by dystonia were tested. A broad contralateral γ band (35-105 Hz) ERS occurred at movement onset with a maximum reached at peak velocity of the movement. The pallidal oscillatory γ activity correlated with movement parameters: the larger and faster the movement, the stronger was the synchronization in the γ band. In contrast, the event-related decrease in beta band activity was similar for all movements. Gamma band activity did not change with movement direction and did not occur during passive movements. The stepwise increase of γ activity with movement size and velocity suggests a role of neuronal synchronization in this frequency range in basal ganglia control of the scaling of ongoing movements.